A Comparative Study and Automated Detection of Illegal Weapon Procurement over Dark Web. Issue 5 (4th July 2019) - Saini, Jaspal Kaur; Bansal, Divya
Abstract: Terrorist groups have reconnoitered smarter ways to use online discussion forums for their violent plans. They have been using their privately owned discussion forums for various illegal purposes. A comparative study of work done on various dark web forums of terroristic organizations is done in this paper. This paper proposes a novel approach to identify procurement of modern weapons over the social media forum by terrorist groups. We used data from four dark web forum websites named "Ansar Aljihad Network", "IslamicAwakening", "Gawaher", and "IslamicNetwork" . Multiple experts independently annotated 313 randomly selected posts as procurement (YES) or non- procurement (NO) to label the forum threads. Mutual agreement between experts is computed to find the level of significance. Furthermore, we used machine learning classification techniques (MLCT) in order to classify labeled posts. To our knowledge, our procurement model presents a first of its kind model to automatically detect procurement of modern weapons over dark web. The work done presents application of social media analytics and text mining to counter terrorism.